2017
DOI: 10.1002/acr.23153
|View full text |Cite
|
Sign up to set email alerts
|

Telerheumatology: A Systematic Review

Abstract: Objective The aim of this systematic review was to identify and summarize the published literature on the use of telemedicine for the diagnosis and management of inflammatory and/or autoimmune rheumatic disease. Methods We performed a registered systematic search (CRD42015025382) for studies using the MEDLINE (1946-August 2015), Embase (1974-August 2015), Web of Science (1900-August 2015), and Scopus (1946-August 2015) databases. We included studies which demonstrated the use of telemedicine for diagnosis an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
140
0
5

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 159 publications
(151 citation statements)
references
References 52 publications
(43 reference statements)
6
140
0
5
Order By: Relevance
“…In a randomized controlled study from 1989, Weinberger et al found tele‐consultations to improve physical health in patients with osteoarthritis . However, no studies have yet investigated the effect of monitoring disease activity through a tele‐health followup strategy in patients with RA , and most of the evidence on the efficacy of tele‐health interventions in chronic diseases is derived from studies within heart disease, obstructive lung disease, asthma, diabetes mellitus, and hypertension . This indicates, however, that tele‐health interventions seem to be both effective and time saving, as well as associated with a high degree of patient satisfaction .…”
Section: Introductionmentioning
confidence: 99%
“…In a randomized controlled study from 1989, Weinberger et al found tele‐consultations to improve physical health in patients with osteoarthritis . However, no studies have yet investigated the effect of monitoring disease activity through a tele‐health followup strategy in patients with RA , and most of the evidence on the efficacy of tele‐health interventions in chronic diseases is derived from studies within heart disease, obstructive lung disease, asthma, diabetes mellitus, and hypertension . This indicates, however, that tele‐health interventions seem to be both effective and time saving, as well as associated with a high degree of patient satisfaction .…”
Section: Introductionmentioning
confidence: 99%
“…Patients may also need to consider the feasibility of attending frequent outpatient appointments, particularly as patients often have to travel significant distances to clinics in NZ as in Canada. Patient‐completed remote monitoring tools and tele‐rheumatology may be required to aid in the frequent review of patients in order to individualize their care within an RA T2T protocol …”
Section: Discussionmentioning
confidence: 99%
“…33 A systematic review on tele-rheumatology published in 2017 concluded that it is very good for the follow-up of patients diagnosed with RA. 38 Comparison of teleconferencing with a remote center with in-person consultation led to similar control of disease activity. However, it was felt that patient preference should be taken into account when offering these services as there was a significant dropout in both arms.…”
Section: Aplar Has Recently Started An Aplar -European League Againstmentioning
confidence: 99%
“…A systematic review on tele‐rheumatology published in 2017 concluded that it is very good for the follow‐up of patients diagnosed with RA . Comparison of teleconferencing with a remote center with in‐person consultation led to similar control of disease activity.…”
Section: Solutionsmentioning
confidence: 99%